Selective fluorescence sensing of H2PO4− by the anion induced formation of self-assembled supramolecular polymers. Issue 20 (10th March 2020) - Sabater, Paula; Zapata, Fabiola; Bastida, Adolfo; Caballero, Antonio
Abstract : H2 PO4 − anions induced the formation of a fluorescent supramolecular polymer by halogen bonding interactions in a bromoimidazolium based tripodal receptor. Abstract : The utilization of anions to induce the formation of self-assembled supramolecular polymers in solution is an undeveloped area of host–guest chemistry. We report in this manuscript a comparative study of two tripodal anion receptors by hydrogen or halogen bonding interactions to form self-assembled supramolecular structures induced by the presence of anions. DOSY NMR and DLS experiments provided evidence for the formation of supramolecular structures in solution in both halogen and hydrogen bond donors with H2 PO4 − anions. The nucleation and elongation constants obtained using the thermodynamic model indicate that the polymers grow following an isodesmic mechanism. Emission studies demonstrate that only the formation of the supramolecular polymer between the halogen bond donor receptor and H2 PO4 − anions results in the appearance of the excimer emission band.